2004
DOI: 10.1095/biolreprod.103.024125
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Prohibitin Expression During Follicular Development and Atresia in the Mammalian Ovary1

Abstract: Prohibitin is a ubiquitous and highly conserved protein implicated as an important regulator in cell survival. Prohibitin content is inversely associated with cell proliferation, but it increases during granulosa cell differentiation as well as in earlier events of apoptosis in a temperature-sensitive granulosa cell line. In the present study, we have characterized the spatial expression patterns for prohibitin using established in vivo models for the induction of follicular development and atresia in the mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 40 publications
1
51
0
Order By: Relevance
“…In contrast, studies from many laboratories, including ours have attributed a predominantly nuclear function for prohibitin (13-16, 24, 26, 53-55). It has been shown recently that prohibitin is localized to the nucleus and cytoplasm of LnCAP cells (55); similarly, studies on prohibitin in rat ovary showed that prohibitin translocated from the cytoplasm to the nucleus in atretic follicles (54). A protein very similar to prohibitin (prohibitin 2, REA, and BAP37) has been described to repress the transcriptional activity of the estrogen receptor (18,19) as well as myoD (20).…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, studies from many laboratories, including ours have attributed a predominantly nuclear function for prohibitin (13-16, 24, 26, 53-55). It has been shown recently that prohibitin is localized to the nucleus and cytoplasm of LnCAP cells (55); similarly, studies on prohibitin in rat ovary showed that prohibitin translocated from the cytoplasm to the nucleus in atretic follicles (54). A protein very similar to prohibitin (prohibitin 2, REA, and BAP37) has been described to repress the transcriptional activity of the estrogen receptor (18,19) as well as myoD (20).…”
Section: Discussionmentioning
confidence: 91%
“…Besides, a different role of prohibitin in cancer cells as a crucial prerequisite for cell proliferation and survival was reported, which seemed to be associated with adhesion or migration signaling, and most likely as chaperones and scaffolding proteins as in mitochondria [23]. However, it is unknown if prohibitin plays any role in ovarian epithelial cells, particularly in the process of OET development, although prohibitin does have biological function in folliculogenesis [24]. In contrast to those in normal ovarian epithelium, a higher prohibitin expression level was observed in ovarian papillary serous and endometrioid carcinomas, which was inversely associated with cellular Ki-67 expression, a marker of cell proliferation and positively correlated with the cell survival marker X-linked inhibitor of apoptosis protein (XIAP).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work considered prohibitin as a potential tumor suppressor gene because microinjection of prohibitin transcripts resulted in growth arrest in HeLa cells (11). Prohibitin has also been reported to be localized to the nuclei of breast cancer cells (12) and to mediate hormone response in prostate cancer and ovary granulosa cells (13,14). There is evidence for the interaction of prohibitin with the cell cycle checkpoint molecules, including E2F (15), p53 (12), and pRB (16,17), and the overexpression of prohibitin can modulate transcription of multiple genes in the transfection experiments.…”
Section: Introductionmentioning
confidence: 99%